Application status of MALDI-TOF mass spectrometry in the identification and drug resistance of Mycobacterium tuberculosis - Zhang, Ruixue; Long, Yin; He, Wenfang; Hao, Xiaoke; Liu, Jiayun (Journal of Thoracic Disease, 2014)
The article “Application status of MALDI-TOF mass spectrometry in the identification and drug resistance of Mycobacterium tuberculosis” (doi: 10.3978/j.issn.2072-1439.2014.02.19) that appeared on page 512-516 of the May 2014 issue of the Journal of Thoracic Disease needs to be withdrawn due to some misconduct in the manuscript. We are sorry for the inconvenience caused.